Zakat Management and Capital Assistances Programme in Brunei Darussalam - Bashir, M. S.; Haji Sarbini, H. N. A.; Abdullah, H. R. (Universiti Sains Islam Malaysia, 2024)
There are different point of views with regards to mechanism of zakat distribution, especially how much the share, which should be received by each item. Zakat has special characteristic that distinguishes zakat from other transfers of wealth which is that zakat can only be used in the limited objectives. These objectives are related to individual, community and humanity at large. As well as being an obligatory act of worship, it is a system through which a Muslim society can eradicate poverty and inequalities. The purpose of this paper is to examine the system of zakat management in Brunei Darussalam including the collection and disbursement channels handled by the Zakat Collection and Disbursement Division (BAKAZ) in Brunei Darussalam. This paper identifies the categories of zakat recipients (asnaf) and application recognized in Brunei Darussalam. It is interesting to note that there has been significant increase in the number of recipients of zakat fund from the category of destitute and poor since the year 2004, although there was evidence of a decrease in zakat received on property in 2006 and 2007 which could be the result from lack of fund. This paper also highlights the findings of an empirical study regarding the progress and problems faced by the recipients of the capital assistance from the zakat fund. As resulted from the findings and observations, this paper provides some policy implications in order to improve the efficiency anf effectiveness of Zakat management in Brunei.